Sustainable Cities in Developing Countries: A Case of Balancing Cultural Heritage Preservation and Tourism in Manila, Philippines - Cruz, Geoffrey Rhoel C. (Animo Repository, 2024)
This study argues that heritage can work side-by-side with development, with culture and heritage serving as an integral part of the city’s economic backbone. A major challenge faced by developing countries is making their cities sustainable by preserving cultural heritage amidst demands for economic growth. This is experienced in the Philippines, with its capital city, Manila, as a case in point. Using a heritage-driven development framework developed by Zerrudo (2020), the paper examines how cultural heritage conservation and tourism development objectives affect the sustainability of cities in developing countries. The paper emphasizes culture as an important pillar of sustainable development. Through online key informant interviews and stakeholder analysis, this qualitative study investigates the tension among stakeholders involved in heritage conservation and tourism development as they push for their divergent interests. The identified conflict stems from the lack of awareness on the part of the stakeholders concerning heritage preservation, which leads to the destruction of built cultural heritage. The findings present that a sustainable urban revitalization program can effectively promote a creative economy that can generate employment opportunities and improve the existing economic conditions, especially for low-income citizens who are part of the city’s humanscape.